2019
DOI: 10.1042/bsr20190152
|View full text |Cite|
|
Sign up to set email alerts
|

Taenia soliumandTaenia crassiceps: miRNomes of the larvae and effects of miR-10-5p and let-7-5p on murine peritoneal macrophages

Abstract: Neurocysticercosis (NCC), a major cause of neurological morbidity worldwide, is caused by the larvae of Taenia solium. Cestodes secrete molecules that block the Th1 response of their hosts and induce a Th2 response permissive to their establishment. Mature microRNAs (miRs) are small noncoding RNAs that regulate gene expression and participate in immunological processes. To determine the participation of Taenia miRs in the immune response against cysticercosis, we constructed small RNA (sRNA) libraries from lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…These five miRNAs account for ~90% of miRNA expression [17]. These miRNAs and miR-4989 were also highly expresses in Taenia solium cysticerci [27]. Coincidentally, in other reports of small RNAs from cestodes that used the same methodology for miRNA discovery, miR-10, let-7, miR-71 and bantam were the most highly expressed, suggesting important functions in cestode biology [20,21,23,24].…”
Section: Mirnas In Taenia Solium and Taenia Crassicepsmentioning
confidence: 80%
See 1 more Smart Citation
“…These five miRNAs account for ~90% of miRNA expression [17]. These miRNAs and miR-4989 were also highly expresses in Taenia solium cysticerci [27]. Coincidentally, in other reports of small RNAs from cestodes that used the same methodology for miRNA discovery, miR-10, let-7, miR-71 and bantam were the most highly expressed, suggesting important functions in cestode biology [20,21,23,24].…”
Section: Mirnas In Taenia Solium and Taenia Crassicepsmentioning
confidence: 80%
“…Already knowing that the more abundant miRNAs (miR-10-5p, let-7-5p) putatively have target genes of immune response and that macrophages in murine cysticercosis promote Th1 or Th2 responses it was demonstrated that synthetic miR-10-5p and let-7-5p were internalized into the cytoplasm of murine peritoneal macrophages in vitro [27]. Interestingly, the down regulation of the expression of pro-inflammatory cytokines, such as Il6, Il1b, and TNF, IL-12, was reported when activated macrophages were incubated with IFN-γ and miR-10-5p or let-7-5p.…”
Section: Mirnas and Immune Responsementioning
confidence: 99%
“…In mice, the miR-10a targets Prdm1 gene to suppress the production of IL-10 in CD4 + T cells, playing important roles in regulation of intestinal homeostasis and in pathogenesis of autoimmune diseases ( 42 ). The parasites Taenia solium and T. crassiceps produce an abundance of miR-10-5p, which is important for establishment of immunosuppressive mechanisms in the host by acting on host cells to regulate expression of proinflammatory cytokines in macrophages M(IFN-γ) and anti-inflammatory cytokines in macrophages M(IL-4) ( 43 ). As the novel identified miRNA, miR-10c has a base different from known miR-10 and miR-10a in the seed region, and its targeting genes may be different from those of miR-10.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant miR-10-5p and let-7-5p in Taenia solium and Taenia crassiceps characterized immunosuppressive effects on murine peritoneal macrophages, which strongly decreased the expression of interleukin 6 (IL-6), tumor necrosis factor (TNF) and interleukin (IL-12) secretion. They also moderately decreased nitric oxide synthase inducible (NOS2) and Il1b expression (pro-inflammatory cytokines) in M (IFN-γ) macrophages, expression of Tgf1b, and the secretion of IL-10 (anti-inflammatory cytokines) in M (IL-4) macrophages [37]. miRNA let-7-5p from C. pisiformis exosomes has been reported to decrease M1 phenotype expression while promoting polarization to the M2 phenotype through inhibition of the expression of transcription factor CCAAT/enhancer-binding protein (C/EBP)-δ.…”
Section: Discussionmentioning
confidence: 99%